DiN EGiTiMiNiN HEDEFLERi - Oruç, Cemil (Fırat University, 2008)
The problems that modern societies face taday are ınany; soıne are due to natural disasters !ike eartlıquakes and floods; atlıers are mannıade ones !ike wars and conflicts; soıne have physical affects, and others have moral and spiritual implications. Tlıere are many problenıs we have to overcoıne. If these probleıns are not tackled effectively, they will soan turn to be threats for us all. W e believe that one of the most effective steps to solve such problenıs is to establislı ways for strong religion education. Such an education will not only help to educate the human being, but alsa contribute to develop the societies and cultures. From the beginning dates, Islam religion that developed an education understanding deterınined same objectives for human beings. These are the see u lar objectives and the afıerdeaılı
The Objectives of the Religion Education
Keywords: Religious Studies; Din Araştırmaları